Pelatihan penggunaan vakum sealer untuk mempertahankan kadar air dan memperpanjang umur simpan ikan asin pada produsen ikan asin di Desa Layeun Kecamatan Leupung - Hadi, Abdul; Mulyani, Nunung Sri; Wagustina, Silvia; Al Rahmad, Agus Hendra (Politeknik Kesehatan Kemenkes Aceh, 2025)
Microbiological deterioration of fish is caused by microbial contamination or spoilage microbes. One technique to extend the shelf life and maintain the sensory quality of a food product is vacuum packaging. The principle of vacuum packaging is to remove all air from the package, then close it tightly so that a condition without oxygen is created in the package. The absence of oxygen can inhibit the growth of destructive microorganisms and chemical reactions, thus extending the shelf life of the packaged product. This community service activity aims to increase community knowledge, especially salted fish producers in order to extend the shelf life of salted fish. From the results of the acquisition of the average value of knowledge and attitudes of participants who took the pre-test and post-test, it was seen that there was an increase in participant knowledge by 6%, from 70,33% to 76,33%. There was an increase in the average attitude of participants by 1,34%, from 84,33 to 85,67%. Training on the use of vacuum sealers to maintain moisture content and extend the shelf life of salted fish in salted fish producers in Layeun Village, Leupung District has a positive impact on increasing knowledge and attitudes towards salted fish preservation. Keywords: Vacuum Sealer, Salted Fish, Shelf Life